1996
DOI: 10.1038/bjc.1996.18
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine in patients with advanced pancreatic cancer

Abstract: Summary The efficacy and safety of gemcitabine at a starting dose of 800 mg m2 administered once a week for 3 weeks with 1 week's rest was investigated in chemonaive patients with advanced and/or metastatic pancreatic cancer. Of 34 patients, 32 were evaluable for efficacy, 20 patients had metastatic stage IV disease, 25 had a performance status of I and 26 (76%) patients has significant pain on presentation. All responses were independently validated by an external oncology review board: two patients achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
160
1
5

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(171 citation statements)
references
References 9 publications
5
160
1
5
Order By: Relevance
“…Recently, there has been renewed interest in single -agent chemotherapy with the advent of novel agents such as irinotecan (response rate 11%) (Sakata et al, 1993) and docetaxel (response rate 20%) (Androulakis et al, 1999). Single-agent GEM has also been recently investigated for activity as well as toxicity in advanced pancreatic cancer by Casper et al, 1994 andCarmichael et al, 1996, who reported modest objective response rates of 6.3 -11% and median survivals of 5.6 -6.3 months; however, the symptomatic improvements were greater than the objective tumour response rates would suggest. Consequently, the National Cancer Institute and the Food and Drug Administration (USA) have accepted that the relief of tumourrelated symptoms is itself a noteworthy goal of carcinoma treatment (O'Shaughnessy et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been renewed interest in single -agent chemotherapy with the advent of novel agents such as irinotecan (response rate 11%) (Sakata et al, 1993) and docetaxel (response rate 20%) (Androulakis et al, 1999). Single-agent GEM has also been recently investigated for activity as well as toxicity in advanced pancreatic cancer by Casper et al, 1994 andCarmichael et al, 1996, who reported modest objective response rates of 6.3 -11% and median survivals of 5.6 -6.3 months; however, the symptomatic improvements were greater than the objective tumour response rates would suggest. Consequently, the National Cancer Institute and the Food and Drug Administration (USA) have accepted that the relief of tumourrelated symptoms is itself a noteworthy goal of carcinoma treatment (O'Shaughnessy et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported encouraging results with single chemotherapy agents or combination treatments (Mallinson et al, 1980;Casper et al, 1994;Palmer et al, 1994;Carmichael et al, 1995;Burris et al, 1997) and gemcitabine has been compared to 5-fluorouracil (5-FU) in a phase III study in patients with advanced pancreatic cancer (Burris et al, 1997). The results of this study suggested that patients receiving gemcitabine had both an improved survival and patient benefit compared to those patients receiving 5-FU and these data and data from several other studies have led to the widespread acceptance of gemcitabine as first-line therapy in patients with advanced pancreatic cancer Carmichael et al, 1995;Rothenberg et al, 1996;Burris et al, 1997;Storniolo et al, 1999).…”
mentioning
confidence: 99%
“…Gemcitabine undergoes intracellular phosphorylation to the active metabolites gemcitabine diphosphate and gemcitabine triphosphate, leading to inhibition of ribonucleotide reductase and incorporation of gemcitabine triphosphate into DNA and RNA (Xu and Plunkett, 1992;Ruiz van Haperen et al, 1993). It is active against non-small-cell lung cancer, pancreatic cancer, breast cancer and ovarian cancer (Abratt et al, 1994;Lund et al, 1994;Carmichael et al, 1995Carmichael et al, , 1996. A review of gemcitabine safety profile establishes this drug as a relatively safe antimetabolite, with adverse events that generally are manageable and reversible, rarely leading to discontinuation of the drug.…”
mentioning
confidence: 99%